Operationalising forensic genetic genealogy in an Australian context. (November 2020) - Scudder, Nathan; Daniel, Runa; Raymond, Jennifer; Sears, Alison
Highlights: Forensic genetic genealogy, a technique that uses public genetic databases, raises technical and process considerations. This article explores considerations such as feasibility for investigators, scientific validation and an assessment of cost. The article reviews legal issues, in an Australian context, for laboratories considering using this capability for casework. Abstract: Forensic genetic genealogy, a technique leveraging new DNA capabilities and public genetic databases to identify suspects, raises specific considerations in a law enforcement context. Use of this technique requires consideration of its scientific and technical limitations, including the composition of current online datasets, and consideration of its scientific validity. Additionally, forensic genetic genealogy needs to be considered in the relevant legal context to determine the best way in which to make use of its potential to generate investigative leads while minimising its impact on individual privacy. This article presents these issues from an Australian perspective, with the observations and conclusions likely to be applicable to other jurisdictions.